AB0004 Characterization of Putative Pre-RA Signatures by Transcriptome Analysis. (9th June 2015) - Petit-Teixeira, E.; Derbois, C.; Dalmasso, C.; Olaso, R.; Ambroise, C.; Ben Kilani, M.S.; Deleuze, J.-F.; Gabay, C.; Cornelis, F.; Finckh, A.
Abstract : Background: Currently, the general understanding of the RA development is that the RA biological initiation precedes the clinical onset of the disease by up to several years. To identify new risk factors and pre-RA biomarkers that would detect specific disease development of pre-clinical phases and eventually predict disease onset and outcome, sampling in new large cohorts of asymptomatic individuals was initiated. Characterization of such individuals at high risk of developing RA will provide helpful strategies for early preventive treatment of RA. Objectives: Benefiting of such a cohort collected in Switzerland, we aimed to characterize whole expression profile using blood samples from healthy first degree relatives of RA. A differential expression study was performed after stratification regarding clinical symptoms onset during follow-up. Methods: Whole transcriptome analysis was performed with Illumina HumanHT-12 v4 Expression BeadChip using RNAs extracted from blood samples of 69 healthy first degree RA relatives. During the follow-up, 15 out of 69 became symptomatic with at least one swollen or tender joint. After differential expression analysis, bioinformatics tools were used to identify pathways and/or biological process enrichment. Results: Controlling the false discovery rate at 0.5 level to optimize detection of putative signatures, we identified a list of 201 differentially expressed genes. Several pathways and biological process have been highlighted through this gene list. Conclusions: This preliminary study provides candidate gene expression signatures which could be relevant for the development of RA. These candidate signatures have to be tested for their RA predictive value in a new sample set from first degree RA relatives from a French similar cohort and molecular validation of genes differentially expressed has to be performed. Follow-up of individuals will allow stratification of symptomatic relatives considering rheumatoid arthritis development, to refine expression signatures. Disclosure of Interest: None declared